2010
DOI: 10.1002/clc.20576
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Contrast‐induced Nephropathy: A Single Center Randomized Study

Abstract: Background: Contrast-induced nephropathy (CIN) is the third cause of acute deterioration of renal function in hospitalized patients. Hypothesis: The purpose of the study was to compare the efficacy of saline infusion, saline infusion plus N-acetylcysteine (NAC), and sodium bicarbonate (SB) infusion to prevent CIN in patients undergoing coronary angiography and/or percutaneous coronary intervention. Methods: We prospectively studied 156 patients with a baseline creatinine level ≥1.2 mg/dL. The primary endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Our results also show that oxidative injury plays an important role in FA-induced AKI, but that NAC is only effective for prevention not treatment. This study has thus confirmed and extended the observation that NAC is only effective in preventing AKI induced by nephrotoxic substances, but worsens AKI when given for treatment, at least under some conditions (19, 20, 21). While our results cannot be directly translated into clinical practice, they do raise important cautionary notes regarding the use of NAC in the clinical setting.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results also show that oxidative injury plays an important role in FA-induced AKI, but that NAC is only effective for prevention not treatment. This study has thus confirmed and extended the observation that NAC is only effective in preventing AKI induced by nephrotoxic substances, but worsens AKI when given for treatment, at least under some conditions (19, 20, 21). While our results cannot be directly translated into clinical practice, they do raise important cautionary notes regarding the use of NAC in the clinical setting.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the more severe the AKI is, the higher levels of the free iron are. It may explain why NAC was not effective in severe AKI in previous studies (16, 21). In severe sepsis, NAC treatment even aggravated organ failure (38).…”
Section: Discussionmentioning
confidence: 87%
“…Forty-eight eligible RCTs15–62 enrolled 14 709 patients with CKD undergoing CAG±PCI. Figure 1 shows the results of the search and the number of citations at different stages of the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies focused on the comparative effectiveness of IV sodium bicarbonate (bicarbonate) and IV sodium chloride (saline) based on the hypothesis that alkalinization of tubular fluid with bicarbonate will decrease the generation of injurious reactive oxygen species. Several trials suggested bicarbonate to be more effective than saline (5)(6)(7)(8)(9)(10)(11)(12), whereas others reported no difference (13)(14)(15)(16)(17)(18)(19)(20)(21). A second preventive intervention that has received substantial attention is the administration of N-acetylcysteine (NAC), an antioxidant with vasodilatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…All used nominal changes in kidney function as the primary endpoint and most did not systematically track longer-term, patient-centered outcomes. Some used differing protocols for the administration of bicarbonate and saline, further complicating interpretation of the key results related to fluid composition (12,15,16,18,19).…”
Section: Introductionmentioning
confidence: 99%